Research Status of Cultivated Land Quality Evaluation in Shaanxi Province - Niu, Yan; Ye, Shenglan; Zhang, Lu; Song, Xinkun (International Journal of Agriculture and Food Sciences Research, 2025)
The cultivated land resources in Shaanxi Province show significant differences between the north and the south, which can be divided into three regions: the Loess Plateau in northern Shaanxi, the Guanzhong Plain, and the Qinba Mountains in southern Shaanxi. The quality grades present a pyramid shape, with medium and low-yield fields accounting for more than 70%. There are problems such as low soil organic matter content, residual mulch films, and high pesticide application intensity. Currently, measures such as the "Fertile Soil Project" have been implemented to initially establish a quality protection system. In terms of evaluation methods, the Analytic Hierarchy Process (AHP) enables structured decision-making, but the weight assignment is vulnerable to subjective influences. The Fuzzy Comprehensive Evaluation Method is good at handling fuzzy information, yet it has the problem of "centralized results". The GIS spatial analysis method has obvious advantages in large-scale evaluations, but it has high requirements for data and costs. The Principal Component Analysis (PCA) can reduce dimensions, but the physical meaning is ambiguous. Machine learning methods can handle complex relationships, but they have the "black box" problem. In the future, the cultivated land quality evaluation in Shaanxi Province will develop towards intelligence and dynamism. It will promote the integration of space-air-ground monitoring, establish a dynamic monitoring system, formulate evaluation specifications, innovate mechanisms, build a collaborative governance system, and form a closed-loop management system covering the whole chain of "monitoring-evaluation-governance-control".